Nucleus–Plasma Membrane Contact Sites Are Formed During Spermiogenesis in the Acoel - Matthew J. Hayes; Anne-C. Zakrzewski; Timothy P. Levine; Maximilian J. Telford (Contact, 2020)
Symsagittifera roscoffensis is a small marine worm found in the intertidal zone of sandy beaches around the European shores of the Atlantic. S. roscoffensis is a member of the Acoelomorpha, a group of flatworms formerly classified with the Platyhelminthes, but now recognized as Xenacoelomorpha, a separate phylum of disputed affinity. We have used electron microscopy to examine the process of spermiogenesis (the final stage of spermatogenesis) in S. roscoffensis , by which spermatids form highly elongated spermatozoa. Their nuclei are long and thread-like, running most of the cell’s length, and during the process, a pair of flagella are fully incorporated into the cell body. Two previously undescribed interorganelle contact sites form at different stages of spermiogenesis. Strikingly, there is an extensive nucleus–plasma membrane contact site. Golgi-derived granules containing electron-dense filaments line up along the spermatid plasma membrane, undergo a conformational change, and donate material that forms a perinuclear layer that cements this contact site. We also show in spermatids at an earlier stage that the same granules are associated with microtubules, presumably for traffic along the elongating cell. We identify a second spermiogenesis-specific contact site where sheaths engulfing each internalizing flagellum contact the nuclear envelope.